2014
DOI: 10.1371/journal.ppat.1003831
|View full text |Cite
|
Sign up to set email alerts
|

A Single Amino Acid in the Stalk Region of the H1N1pdm Influenza Virus HA Protein Affects Viral Fusion, Stability and Infectivity

Abstract: The 2009 H1N1 pandemic (H1N1pdm) viruses have evolved to contain an E47K substitution in the HA2 subunit of the stalk region of the hemagglutinin (HA) protein. The biological significance of this single amino acid change was investigated by comparing A/California/7/2009 (HA2-E47) with a later strain, A/Brisbane/10/2010 (HA2-K47). The E47K change was found to reduce the threshold pH for membrane fusion from 5.4 to 5.0. An inter-monomer salt bridge between K47 in HA2 and E21 in HA1, a neighboring highly conserve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
145
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(151 citation statements)
references
References 35 publications
6
145
0
Order By: Relevance
“…Surveillance reports after the 2009 pandemic identified another HA-stabilizing mutation (HA2-E47K) that may have played a role in adaptation of pH1N1 to humans (29,30). Other viral genes may also contribute to pandemic capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Surveillance reports after the 2009 pandemic identified another HA-stabilizing mutation (HA2-E47K) that may have played a role in adaptation of pH1N1 to humans (29,30). Other viral genes may also contribute to pandemic capacity.…”
Section: Discussionmentioning
confidence: 99%
“…54 A stabilising mutation present in more recent pH1N1 isolates but not the earliest strains from 2009 was associated with greater infectivity in the ferret nasal tract. 55 O'Donnell et al 56 demonstrated that viruses reassorted to contain "Ann Arbor" internal genes became less pH stable than their wild-type counterparts due to cold-adapting mutations in the viral M gene. This reduction in stability could have greater impact on infectivity of pH1N1, which may already exist closer to the threshold for inactivation in the upper respiratory tract.…”
Section: (Iii)biological Characteristics Of the Ph1n1 Virus (A)reducementioning
confidence: 99%
“…60 In response to this, vaccine manufacturers took the initiative to update the pH1N1 component of LAIV in their 2015/16 product to include the HA from a more recent pH1N1 isolate (A/Bolivia/559/2013) that contains a known HA stabilising mutation 55 . In addition, measures were taken to improve maintenance of the cold chain.…”
Section: (B)reduced Thermostability Of the Ph1n1 Componentmentioning
confidence: 99%
“…Potential interference among viruses included in the LAIV4 cannot be excluded but is not consistent with the results reported when the immunogenicity of LAIV4 was compared with that of LAIV3. 75 Heat susceptibility may have played a role, at least for the poor vaccine effectiveness in 2013-2014. During that influenza season, LAIV was prepared with the A/California/7/ 2009pdm09 strain.…”
Section: Characteristicsmentioning
confidence: 99%